2020
DOI: 10.1111/jan.14716
|View full text |Cite
|
Sign up to set email alerts
|

Integrative literature review of evidence‐based patient‐centred care guidelines

Abstract: Aim To summarize what facilitates patient‐centred care for adult patients in acute healthcare settings from evidence‐based patient‐centred care guidelines. Design An integrative literature review. Data sources The following data sources were searched between 2002‐2020: Citation databases: CINAHL, Medline, Biomed Central, Academic Search Complete, Health Source: Nursing/Academic Edition and Google Scholar. Guideline databases: US National Guideline Clearinghouse, Guidelines International Network, and National I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 28 publications
0
19
0
2
Order By: Relevance
“…The presented findings showed that patients who lived with their spouse or someone else were generally more satisfied with care than patients who lived alone. Family involvement in patient care has been found to increase patient satisfaction, particularly in situations related to patient education and discharge planning [ 40 ]. In addition, Giap and Park (2021) found that interventions that promote patient and family involvement can reduce the prevalence of adverse events, decrease the length of a hospital stay, improve patient perceptions of safety, and improve patient satisfaction [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presented findings showed that patients who lived with their spouse or someone else were generally more satisfied with care than patients who lived alone. Family involvement in patient care has been found to increase patient satisfaction, particularly in situations related to patient education and discharge planning [ 40 ]. In addition, Giap and Park (2021) found that interventions that promote patient and family involvement can reduce the prevalence of adverse events, decrease the length of a hospital stay, improve patient perceptions of safety, and improve patient satisfaction [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The art of treatment includes SDM as a shift toward personalized medicine [18]. Different variables play a role in SDM role in Poland, which are universal ones: contact between the doctor and the patient, the degree of reduction of control and power of medical personnel, consent to patient independence, and knowledge sharing [19]. What seems to be urgent to solve in Poland is a lack of guidelines and recommendations, including an SDM.…”
Section: The Role Of Patients' Organizationsmentioning
confidence: 99%
“…-the democratization of knowledge -dissemination of sources of scientific knowledge [19], popularization of knowledge by the media, the phenomenon of intelligent crowds (dispersed, collective knowledge available on the Internet -creating social networks around selected health problems [20]); -an increasing level of proficiency in society; -diminishing trust in expert systems [18]; -disseminating participatory models in other spheres of social life (social consultations, engaging citizens in creating public policies, creating civil society (institutions support, patient citizens, e.g., organizations acting for patients); -genuine commitment and willingness to understand the individuality of patients; -cultural context [21].…”
Section: The Role Of Patients' Organizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This increased focus on the patient perspective in healthcare research has been driven, in part, by recent US Food and Drug Administration (FDA) Patient-Focused Drug Development (PFDD) guidance [ 1 ]. This shift is also reflected in wider patient engagement initiatives, including more involvement of patient advocates in HTA decision making [ 6 ], organisations like the British Medical Journal and the Patient-Centred outcomes Research Institute involving patient advocates in their article and grant development processes [ 7 , 8 ], and an increased emphasis on patient-centredness in clinical settings [ 9 , 10 ]. All these patient-centric activities ultimately aim to support better service outcomes and increased patient satisfaction.…”
Section: Introductionmentioning
confidence: 99%